The Effect of the Read Aloud Method on Students’ Reading Interest at the Elementary Level - Rominah; Yuannisah Aini Nasution; Rizki Lestari (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to determine the effect of the Read Aloud method on the reading interest of third-grade students at SD Negeri 02 Sei Baru. The research was motivated by the low reading interest among students, which has led to limited participation in literacy activities at school. A quantitative approach with a quasi-experimental design was used by comparing pretest and posttest results between the experimental and control classes. Class IIIA served as the experimental group that received treatment using the Read Aloud method, while class IIIB acted as the control group taught with conventional methods. Data were collected using a Likert-scale questionnaire on reading interest. The results showed a significant difference between the posttest averages of the experimental and control classes. The experimental class achieved an average posttest score of 82.15, higher than the control class’s 68.85. The independent t-test produced a significance value of 0.002 (p < 0.05), indicating a significant effect of the Read Aloud method on students’ reading interest. The novelty of this study lies in its focus on implementing the Read Aloud method as a structured literacy intervention within the elementary school curriculum, emphasizing student emotional engagement and interactive storytelling an approach that previous studies have rarely explored in early-grade classroom contexts.